2016
DOI: 10.1111/grow.12159
|View full text |Cite
|
Sign up to set email alerts
|

Servicing Our Economy: Producer Service Location and Government Procurement 2004–2010 in the Washington DC Metropolitan Area

Abstract: Harrington and Campbell (1997) previously illuminated the pattern of producer services' suburbanization in the Washington, D.C., metropolitan area between 1970 and 1992. Their results showed producer services growing at a faster rate at locations farther from the central city. We revisit the topic utilizing data from 2004 to 2010, assessing not only changes in the distribution of producer services since their work, but also the impact of massive increases in defense spending on producer services' growth throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The results revealed producer services employment grew significantly more quickly in the urban D.C. core than the outer suburbs, contrary to Harrington and Campbell's research. Additionally, they found per capita producer services employment was self-limiting over the study period: Locations with more producer services employment in 2004 experienced significantly less producer services growth over the period [13]. Roland (2001) studied the employment structure of producer services in economically undeveloped areas of American Journal of Industrial and Business Management Canada, and found that the relative labor intensity of producer services in these areas was lower than that in large central cities [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed producer services employment grew significantly more quickly in the urban D.C. core than the outer suburbs, contrary to Harrington and Campbell's research. Additionally, they found per capita producer services employment was self-limiting over the study period: Locations with more producer services employment in 2004 experienced significantly less producer services growth over the period [13]. Roland (2001) studied the employment structure of producer services in economically undeveloped areas of American Journal of Industrial and Business Management Canada, and found that the relative labor intensity of producer services in these areas was lower than that in large central cities [14].…”
Section: Literature Reviewmentioning
confidence: 99%